Wanhain Suomalaisten Tawaliset ja Suloiset Sananlascut - Florinus, Henrik, 1633-1705 (Salt Lake City, UT : Project Gutenberg, 2016)
"Wanhain Suomalaisten Tawaliset ja Suloiset Sananlascut" by Henrik Florinus is a collection of traditional Finnish proverbs likely written in the early 18th century. This work aims to preserve the wisdom and knowledge embedded in the Finnish language through its eloquent proverbs. The proverbs included reflect cultural values, insights, and humor pertinent to Finnish society at that time. The opening of the text serves as an introduction to the collection, emphasizing the enduring relevance of proverbs as a vessel of wisdom passed down through generations. It acknowledges the contributions of earlier scholars and clergymen in gathering these sayings, highlighting the importance of language in conveying moral and practical lessons. The preface also invokes a sense of reverence for God and the teachings associated with these sayings, underscoring the blend of spirituality and everyday wisdom that characterizes the collection. (This is an automatically generated summary.)
Release date is 2016-10-10
Produced by Jari Koivisto
Keywords: Proverbs, Finnish